2017
DOI: 10.1080/0886022x.2017.1363778
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transplant histology does not improve prediction of 5-year kidney allograft outcomes above and beyond clinical parameters

Abstract: Pre-implant kidney biopsy is used to determine suitability of marginal donor kidneys for transplantation. However, there is limited data examining the utility of pre-implant histology in predicting medium term graft outcome. This retrospective study examined kidney transplants over a 10-year period at a single center to determine if pre-implant histology can identify cases of eGFR ≤35 ml/min/1.73m at 5 year follow up beyond a clinical predictive logistic regression model. We also compared outcomes of dual kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…As a result, the KDRI/KDPI is not likely to be reliable in isolation to predict graft failure or to decide on discarding donor organs in Ireland. This parallels our findings on histological features of pre-implant kidney biopsies [15].…”
Section: Discussionsupporting
confidence: 91%
“…As a result, the KDRI/KDPI is not likely to be reliable in isolation to predict graft failure or to decide on discarding donor organs in Ireland. This parallels our findings on histological features of pre-implant kidney biopsies [15].…”
Section: Discussionsupporting
confidence: 91%
“…As a registry analysis, the study suffered from selection bias. Two more recent studies compared the predictive performance of a clinical score with the performance of a histological score and found no improvement in prediction of post‐transplant allograft survival beyond the moderate prediction provided by the clinical data . In 2006, Remuzzi et al .…”
Section: Current Methodsmentioning
confidence: 99%
“… 7 Multivariable analysis designed to isolate the impact of each lesion separately found that these findings lose significance when controlled for clinical variables, such as donor age. 24 , 25 Although it must be acknowledged that the outcome of grafts which are not transplanted as a result of biopsy results (“true positives”) is not known, comparison to outcomes from similar organs transplanted in Europe (where biopsy results are not available before transplant) suggests that many of these organs would provide benefit if transplanted. 10 …”
Section: Discussionmentioning
confidence: 99%